2020
DOI: 10.1002/aenm.202001536
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue‐Free Aurivillius Phase Ferroelectric Thin Films with Ultrahigh Energy Storage Performance

Abstract: Dielectric capacitors have become a key enabling technology for electronics and electrical systems. Although great strides have been made in the development of ferroelectric ceramic and thin films for capacitors, much less attention has been given to preventing polarization fatigue, while improving the energy density, of ferroelectrics. Here superior capacitive properties and outstanding stability are reported over 107 charge/discharge cycles and a wide temperature range of −60 to 200 °C of ferroelectric Auriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(78 citation statements)
references
References 53 publications
0
78
0
Order By: Relevance
“…It was indicated that a tensile chemical stress is created by the substitution of larger Fe 2+ and Fe 3+ ions for smaller Ti 4+ in Bi 3.25 La 0.75 Ti 3 O 12 -BiFeO 3 films, which decreases the free energy of the potential well at biased fields, increases the polarization and enhances U e . 60 On the other hand, a compressive chemical pressure induced by Li + /La 3+ ion doping in antiferroelectric (AFE) PbZrO 3 films could stabilize the AFE phase Fig. 3 (a) RSM of BFO-BTO dielectric films around the (103) peaks.…”
Section: Atomic Scale Engineeringmentioning
confidence: 99%
“…It was indicated that a tensile chemical stress is created by the substitution of larger Fe 2+ and Fe 3+ ions for smaller Ti 4+ in Bi 3.25 La 0.75 Ti 3 O 12 -BiFeO 3 films, which decreases the free energy of the potential well at biased fields, increases the polarization and enhances U e . 60 On the other hand, a compressive chemical pressure induced by Li + /La 3+ ion doping in antiferroelectric (AFE) PbZrO 3 films could stabilize the AFE phase Fig. 3 (a) RSM of BFO-BTO dielectric films around the (103) peaks.…”
Section: Atomic Scale Engineeringmentioning
confidence: 99%
“…Normal ferroelectric possesses high P max while its high P r leads to that most of energy is dissipated during the discharge process. By contrast, relaxor ferroelectric exhibits slim P-E loop with high P max and low P r (i.e., high P = P max -P r ) meaning that electric energy can be effectively released, and thus obtains better energy storage performances [60]. Note that strengthening the relaxor characteristics and enhancing E b have become important factors for enhancing W rec .…”
Section: Relaxor Ferroelectric Ceramicsmentioning
confidence: 99%
“…[4][5] Aurivillius phases are established ferroelectric materials with strong in-plane polarisations, 6 high Curie temperatures (600°C) and fatigue-free energy storage performance. [7][8][9] The rare possibility of room temperature ferromagnetism within a ferroelectric framework is achieved in Aurivillius phases with the introduction of magnetic ions within the scaffold. 10-14 15 Bi6TixFeyMnzO18 ( x = 2.80 to 3.04; Y = 1.32 to 1.52; Z = 0.54 to 0.64) 16 where m = 5, is an example of such an ionsubstituted multiferroic Aurivillius phase, displaying saturation magnetization (MS) values of 215 emu/cm 3 , with in-plane saturation polarization (Ps) values of 26 C/cm 2 and with experimentally proven magnetoelectric switching.…”
Section: Introductionmentioning
confidence: 99%